Linguistic study of household vocabulary in English and Uzbek languages - Mashhura Abdujalilova (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the linguistic features of household vocabulary in English and Uzbek, highlighting its role in reflecting cultural traditions, social structures, and communicative practices. The research emphasizes how everyday objects not only meet functional needs but also convey sociocultural values and family dynamics. Research methodology: The study applies a discourse and lexical analysis approach, drawing on explanatory dictionaries, cultural references, and examples from advertisements, conversations, and literature. Comparative analysis between English and Uzbek terms is used to uncover etymological origins, semantic development, and cultural significance. Results: Findings show that household vocabulary carries rich cultural meanings. For instance, words such as mebel and tandir demonstrate how language reflects both foreign influence and indigenous traditions. Household terms also reveal gender roles, family structures, and values of hospitality. Furthermore, modern technologies introduce new terminology, transforming how household items are named and perceived in daily discourse. Conclusions: Household vocabulary is a dynamic linguistic category closely tied to cultural identity and social life. It illustrates the intersection of language, tradition, and modernity, and provides insights into how material culture shapes communication across generations. Limitations: The analysis is limited to English and Uzbek, with reliance on selected dictionaries and cultural references. Broader cross-linguistic comparisons and larger corpora would strengthen generalizability. Contribution: The study contributes to pragmalinguistics and cultural linguistics by showing how domestic lexicon functions as both a linguistic system and a cultural marker, bridging language, identity, and social relations.